Insight into the mechanism of perfluorooctanesulfonic acid adsorption on highly porous media: Sizes of hydrophobic pores and the extent of multilayer formation. (May 2022) - Pauletto, Paola S.; Florent, Marc; Bandosz, Teresa J.
Abstract: Commercial activated carbon (BAX), carbon black (BP2000), and zirconium-based metal-organic framework (UiO–66) were tested as adsorbents of perfluorooctanesulfonic acid (PFOS). They had high surface areas (1500–2000 m 2 /g) and markedly differed in pore size distributions. While UiO–66 was mainly microporous with pore sizes determined by its crystallographic structure, carbonaceous materials had micro/mesoporous structure and mesopores were predominant in carbon black. The efficiency of the PFOS removal and adsorption at equilibrium were tested. The results indicated carbon black as a superior adsorbent on which multilayer of PFOS was formed. Its best performance (81% removal efficiency compared to 55% and 38% on BAX and UiO–66, respectively) was linked to large mesopores of hydrophobic nature. Upon the formation of a monolayer, subsequent layers were formed owing to adsorbate-adsorbent dispersive interactions and the availability of space. It was found that although surface chemistry affected the adsorption process and on carbonaceous materials there is an indication that it even might reduce sulphonic groups, these processes likely took place only during the monolayer formation and therefore their effect on the overall adsorption process decreased in intensity with the formation of subsequent layers. The superiority of carbon materials as PFOS adsorbents over UiO–66 is in the heterogeneity of their pore sizes and in the hydrophobic character of the carbon matrix. Graphical abstract: Image 1 Highlights: Porous carbon black was demonstrated as an efficient adsorbent of PFOS. The shape of adsorption isotherms suggested multilayer process. High volume of mesopores enabled multilayer adsorption via hydrophobic interactions. Surface chemistry markedly affected the adsorption on carbons in the first layer. Oxygen groups were involved in adsorption, and carbon matrix led to –HSO3 reduction.